Data mining methods and an appilcation - Karaca, Babür (My University, 2003)
Veri sondajlama verinin incelenerek daha önce farkedilmemiş ilişkilerin bulunmasına yarar. Analist ve yöneticilere destek olunarak daha önce kendilerinin farkettiği ilişkileri isbat ettiği gibi yenilerinin de keşfedilmesini sağlar. Veri sondajlama araçları makina öğrenim ve istatiksel modelleme tekniklerini kullanır. Farklı amaçlar için kullanılan değişik veri sondajlama tekniklerinin farklı algoritmaları mevcuttur. Her sektör ve şirketin ihtiyaçları farklı olduğundan her problem için aynı teknik ve algoritma uygulanamaz ancak temel olarak metodlar aynıdır. Bu tez çalışmasında veri sondajlamanın satış analizi uygulama alanı incelenmektedir. Kimyasal madde satan bir şirketin bir yıllık satış verisi incelenmekte ve karlılığa etki eden nedenler bulunmaktadır. Ayrıca bu faktörlere göre malzemeler de gruplandırılmaktadır. Yapılan analiz sonucu siparişlerdeki farklı türden ürün adedinin karlılıktaki etkisi görülmüştür. Siparişlerdeki farklı türden ürün adedi arttıkça karlılık azalmaktadır. Bu sonuca bir ürün alana diğer iki ürün bedava şeklinde kampanyaların yol açtığı görülmüştür. Malzemeler karlılığa göre gruplandırılarak yeni ürünler için satış ofisi ve malzeme grubu bazında karlılık tahmini yapılabilecek duruma gelinmiştir. Data mining is used to find unknown patterns from the data. Data mining does not replace skilled business analysts or managers, but rather gives them a powerful new tool to improve the job they are doing. Any company that knows its business and its customers is already aware of many important patterns that its employees have observed over the years. Data mining confirm such empirical observations and find new, subtle patterns. Main aim is to learn not only what happened in the operations, but also why things happened. Data mining tools use machine learning or statistical modelling techniques. These techniques are the conceptual approaches whereas algorithms are the ways of implementing those techniques. Since each company has different requirements, it is not possible to have fixed models for producing prediction results. It is logical to create models according to specific requirements and use these models to draw information from the data to assist decision making. This thesis focuses on sales analysis application in data mining. A chemical producer company's one-year period sales transaction data was explored and affects on profitability were found out. Also products were grouped according to those factors. It was found out that order items is the influencing parameter in the profitability which indicates that as order items increases profitability decreases. Buy one-take three kind of campaigns should be changed to overcome that effect. Also profitability forecasts can be conducted for the new materials according to material group and sales office information which was added to the analysis by the business expertise. It is obvious that adding new attributes, such as, industry or the customer,… should be included in the analysis to increase accuracy of the forecast.
Keywords: Bilgisayar programlaması; Bilgisayar sistemlerinde veri; Genel Konular; kayıt formları; Veri hazırlama ve sunma; Veri Sondajlama